Lavoisiereae (Melastomataceae) na Serra do Caraça, Minas Gerais, Brasil - Brito, Rodrigo Valentim de (2022)
Lavoisiereae is one of the most representative tribes in number of species and with expressive diversity in the Cerrado from Minas Gerais. The present study aimed to inventory and provide the taxonomic treatment of Lavoisiereae species in the Serra do Caraça, Minas Gerais state, Brazil. Based on the exsiccates deposited in Brazilian herbaria and online databases, 33 species are recognized, belonging to Microlicia, with 32 species, and Rhynchanthera, with only one species. Of this total, 22 species of Microlicia are endemic to Minas Gerais, and only M. mendoncaei occurs exclusively in the Serra do Caraça. We also extended the distribution of M. obovatifolia to this mountain range. In addition, two samples were recognized as a taxonomic novelty in Microlicia. We also provide an identification key for the species, morphological descriptions, taxonomic comments, flowering and fruiting, and habitat data.